2009
DOI: 10.1021/jf900517d
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Flavokawain B from Alpinia pricei Hayata

Abstract: Alpinia pricei (Zingiberaceae) is a spicy herb indigenous to Taiwan. A potent anti-inflammatory compound, flavokawain B (FKB), was obtained from A. pricei. FKB significantly inhibited production of NO and PGE(2) in LPS-induced RAW 264.7 cells. Moreover, it also notably decreased the secretion of TNF-alpha. Expression of iNOS and COX-2 proteins was also inhibited by FKB in a dose-dependent manner. FKB blocked the nuclear translocation of NF-kappaB induced by LPS, which was associated with prevention IkappaB deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…The importance of diabetic encephalopathy is increasingly being recognized . Cerebrovascular changes, oxidative stress, increased levels of advanced glycation end products (AGEs) and impaired cerebral insulin signaling systems are considered as the underlying causes of diabetic encephalopathy (Feroz et al, 2012;Lin et al, 2009). Recent data have shown that the accumulation of toxic ␣-oxoaldehydes, such as methylglyoxal (MG), may be a key determinant of cognitive dysfunction (Di Loreto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of diabetic encephalopathy is increasingly being recognized . Cerebrovascular changes, oxidative stress, increased levels of advanced glycation end products (AGEs) and impaired cerebral insulin signaling systems are considered as the underlying causes of diabetic encephalopathy (Feroz et al, 2012;Lin et al, 2009). Recent data have shown that the accumulation of toxic ␣-oxoaldehydes, such as methylglyoxal (MG), may be a key determinant of cognitive dysfunction (Di Loreto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5 One of the several bioactive compounds recently isolated and characterized from Alpinia mutica in our laboratory is flavokawain B (FB), which belongs to the chalcone family of flavonoids ( Figure 1). 6 Several studies have confirmed FB as a potent antiinflammatory, 5 anticancer, 6−8 and antinociceptive 9 agent based on inhibition of the nitric oxide synthase and cyclooxygenase pathways, 5 antiproliferation, and apoptosis of squamous, colon, and prostate cancer cell lines and chemical/ thermal models of nociception in mice, respectively. 6−8 The pharmacokinetics and pharmacodynamics of a particular drug in the human system are greatly affected by its interaction with plasma proteins, as the bioavailability, distribution, and metabolism of biologically active compounds (drugs or natural products) in the body are associated with their affinities to bind to transport proteins of mammalian blood circulation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Rhizomes of Alpinia calcarata root has antnociceptive activities [20,21]. Hence green synthesis of AgNps is demonstrated by reducing the aqueous silver nitrate (AgNO 3 )…”
mentioning
confidence: 99%